Restructuring in France's innovation system: From the mission-oriented model to a systemic approach of innovation - Mafini Dosso (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2014)
The paper discusses the transitional phase of the French innovation system focusing on the activities that influence the development and diffusion of innovations. It shows that the current system combined persistent elements of the traditional mission-oriented model with new systemic institutional structures, thus lengthening the transition towards a new model of innovation. Indeed the introduction of a bulk of reforms in a very short time, the lack of a clear long run agenda, the institutional inconsistencies have blurred the research and innovation policy trajectory and may affect the performances of France's innovation system in the coming years.
Keywords: O30; O31; O38; 330; French innovation policies and system; activities; restructuring